Brief Interventions Influence the Quantity and Quality of Caregiver-Child Conversations in an Everyday Context - Shivaram, Apoorva; Chavez, Yaritza; Anderson, Erin; Fritz, Autumn; Jackson, Ryleigh; Edwards, Louisa; Powers, Shelley; Libertus, Melissa; Hespos, Susan (Frontiers in Psychology, 2021)
Reading and arithmetic are difficult cognitive feats for children to master and youth from low-income communities are often less ‘school ready’ in terms of letter and number recognition skills (Lee & Burkam, 2002). One way to prepare children for school is by encouraging caregivers to engage children in conversations about academically-relevant concepts by using numbers, recognizing shapes, and naming colors (Fisher et al., 2013; Levine et al., 2010). Previous research shows that caregiver-child conversations about these topics rarely take place in everyday contexts (Hassinger-Das et al., 2018), but interventions designed to encourage such conversations, like displaying signs in a grocery store, have resulted in significant increases in caregiver-child conversations (Hanner et al., 2019; Ridge et al., 2015). We investigated whether a brief intervention could change caregiver-child conversations in an everyday context. We observed 212 families in a volunteer-run facility where people who are food-insecure can select food from available donations. Volunteers greet all the clients as they pass through the aisles, offer food, and restock the shelves as needed. About 25% of the clients have children with them and our data consist of observations of the caregiver-child conversations with 2- to 10-year-old children. Half of the observation days consisted of a baseline condition (no signs were displayed) in which the quantity and quality of caregiver-child conversation was observed and volunteers merely greeted the clients. The other half of the observation days consisted of a brief intervention where signs were displayed (signs-up condition). Volunteers greeted the clients and pointed out that there were signs displayed to entertain the children. In addition, there was a within-subject manipulation for the intervention condition where each family interacted with two different categories of signs. Half of the signs had academically-relevant content and the other half had non-academically-relevant content. The results demonstrate that the brief intervention used in the signs-up condition increases the quantity of caregiver-child conversations. In addition, signs with academically-relevant content increase the quality of the conversation. These findings provide further evidence that brief interventions in an everyday context can change the caregiver-child conversation. Specifically, signs with academically-relevant content may promote school readiness.